Hospital adverse outcomes of the elderly in a tertiary referral hospital: A prospective cohort study of 9, 586 admissions. (January 2021) - Moon, Yeonsil; Han, Seol-Heui; Kim, Yoon-Sook; Shin, Jinyoung; Uhm, Kyeong Eun; Jeon, Hong Jun; Choi, Jaekyung; Lee, Jongmin
Highlights: Older adult patients with dysphagia or dementia at admission increased likelihood of falls. The incidence rates of fall, HPU, and mortality were 1.3 %, 4.0 %, and 6.1 %, respectively. Age, admission via ER, low income, fecal incontinence, or functional immobility increased the HPU incidence. Age, male, admission via ER, fecal incontinence, or functional immobility significantly increased hospital mortality. Abstract: Objective: This study aimed to evaluate the hospital adverse outcomes (HAO) of admitted older adult patients in a large prospective cohort and investigate the demographic, economic, and health-related characteristics at risk of HAO in all older adult patients admitted in the general ward of a tertiary referral hospital. Materials and methods: We recruited admission episodes of older adult patients aged over 65 years who were admitted at the general ward of Konkuk University Medical Center, which is a tertiary referral hospital, from September 2016 to October 2017. Out of 9, 586 admission episodes, 8, 263 were included. Modified from the Geriatric Screening for Care-10, six common geriatric health issues, namely, dysphagia, polypharmacy, fecal incontinence, functional mobility, depression, and dementia, were evaluated. Fall, hospital-acquired pressure ulcer (HPU), and mortality were checked daily by experienced nurses during the patients' hospital stay. A logistic regression model was used, and P < 0.05 was the threshold of significance. Results: The incidence rates of fall and HPU were 1.3 % and 4.0 %, respectively. The hospital mortality was 6.1 %. Older adult patients with dysphagia or dementia upon admission were significantly associated with an increased likelihood of falls. Furthermore, age, ER admission, low income, fecal incontinence, or functional immobility increased the HPU incidence. Meanwhile, age, male, ER admission, fecal incontinence, or functional immobility significantly increased the hospital mortality. Conclusion: All demographic, economic, and health-related characteristics, except for polypharmacy and depression, affect the incidence of HAO. Intervention to vulnerable older adult patients with HAO risk could improve the treatment outcome.